Cryptid hunters - Smith, Roland 1951- (Hyperion Books for Children, 2006)
Twins, Grace and Marty, along with a mysterious uncle, are dropped into the middle of the Congolese jungle in search of their missing photojournalist parents.
Keywords: Twins -- Fiction; Brothers and sisters -- Fiction; Uncles -- Fiction; Jungles -- Fiction; Mystery and detective stories; Congo River Valley -- Fiction; Jugendbuch